ANALISIS SENSITIVITAS TURBULENSI ALIRAN PADA KANAL BAHAN BAKAR PWR BERBASIS CFD - Hastuti, Endiah Puji (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
Coolant flow turbulence on heat transfer process serves to enhance the heat transfer coefficient, likewise flow in the fuel sub channel. Computational fluid dynamic program, FLUENT is a computational program based on finite element, that is able to predict and analyze the dynamics of fluid flow phenomena, accurately. CFD calculation program is selected in this study because of its accurately and it also can provide good visualization. Purpose of this research was to understand the characteristics of heat transfer, mass and momentum of the fuel rod to the coolant visually on: the temperature field, pressure field, and the kinetic energy field, as a function of the flow dynamics within fuel channel, on steady state and transient condition. Analysis of flow dynamics in the fuel channel base on CFD was done by using the PWR sample data with reactor power of 1000 MWe on 17x17 array of fuel. To examine the sensitivity of the flow equation in accordance with the model of turbulent flow on fuel channel, the turbulence equation model of k-omega (Ƙ-ω), k-epsilon (Ƙ-ε), and Reynold stress model (RSM) for steady state was used, while for transient turbulence model DES and LES are applied. In the sensitivity analysis of turbulent flow, hexahedral mesh model of three cell geometry each are 0.5 mm, 0.2 mm and 0.15 mm, was selected. The analysis shows that there are similar results of turbulen model Ƙ-ε and Ƙ-ω standard, on steady state analysis. Comparing with Dittus Boelter criteria for Nusselt number, the Reynolds stress model (RSM) is recommended. Sensitivity analysis of mesh geometry between cell size 0.5 mm, 0.2 mm and 0.15 mm, indicating that the cell size of 0.5 mm was sufficient. Developed flow already reached on DES and LES model, however only for short time (3 seconds) for transient condition. LES model need very long computation time and big memory.